Selamat Tinggal Purnama : (Strain Pertama) - Teme Abdullah (Seri Kembangan, Selangor: Iman Publication, 2020)
First Strain. The story of a famous artist. Living in human times had to accumulate enough ?credit? as proof that they were entitled to remain alive on earth.
Keywords: Malaysian fiction (malay); Malay fiction